On τ-closed totally saturated group formations with Boolean sublattices - Safonov, V.G. (Algebra and Discrete Mathematics, 2008)
In the universe of finite groups the description of τ-closed totally saturated formations with Boolean sublattices of τ-closed totally saturated subformations is obtained. Thus, we give a solution of Question 4.3.16 proposed by A.N.Skiba in his monograph "Algebra of Formations" (1997).